Hemoglobin/myoglobin desaturation during speed skating - Rundell, K. W.; Nioka, S.; Chance, B. (Medicine & Science in Sports & Exercise, 1996)
The characteristic low "sitting" position of competitive speed skating has been shown to result in a right shifted heart rate-VO2 curve and elevated submaximal blood lactate values compared with running or cycling. This is thought to be a consequence of reduced blood flow and subsequent oxygen delivery to the exercising muscle while speed skating. Duel wavelength spectrophotometry was used to measure oxygenated and deoxygenated hemoglobin/myoglobin (OD) in the capillary bed of five muscle groups during in-line skating in upright (US) and low (LS) positions. Eight U.S. speed skaters (4 category 1) performed US and LS at 2.68 and 3.13 m.s-1 (4% grade) on a wide (2.44 m) treadmill (4 trials, 5 min each, 20 min recovery between trials). Expired gas parameters and blood lactate (LA) concentrations were determined for each trial. Hip and knee angles were measured (PEAK Motion Analysis) and were significantly different in US and LS. For similar oxygen uptake during US and LS (44.9 +/- 2.79, 45.6 +/- 3.52), heart rate and LA were significantly higher during LS (172 +/- 11 vs 179 +/- 10, 4.35 +/- 2.19 vs 8.70 +/- 3.60). Deoxygenation was significantly greater during LS than during US at both speeds and was greater at 3.13 m.s-1 (P < 0.05). OD was highly related to LA (r > 0.95) but not to whole body VO2. Blood volume change was less for LS than for US (P < 0.05). Increased deoxygenation in the capillary bed of the exercising quadriceps during LS versus US is consistent with the hypothesis that blood flow and subsequent O2 delivery is compromised in the low speed skating position.